Evaluation of the optimum dietary protein level for the maximum growth of juvenile beluga (Huso huso L.1758). Issue 11 (14th February 2013) - Mohseni, Mahmoud; Pourali, Hamid Reza; Kazemi, Rezvan; Bai, Sungchul C
Abstract A 10‐week feeding trial was carried out to evaluate the optimum dietary protein level for the maximum growth of juvenile beluga, Huso huso. Fish averaging 1.34 ± 0.07 g (mean ± SD) was randomly distributed into 18 circular fibreglass tanks of 500 L capacity (20 fish per tank). Six iso‐caloric diets were formulated to contain 30 (CP30), 35 (CP35), 40 (CP40), 45 (CP45), 50 (CP50) and 55% (CP55) crude protein (CP). Fish were fed each of the six experimental diets in triplicate groups. At the end of feeding trial, weight gain (WG) and specific growth rate (SGR) in fish fed CP40 and CP45 diets were significantly higher than those of fish fed CP30, CP35, CP50 and CP55 diets (P < 0.05). Lipid retention increased significantly from 24.7% to 31.6%, but protein retention decreased from 54.6% to 35.6% with increasing protein levels from 30% to 50%. Muscle total essential and non‐essential amino acid (EAA & NEAA) concentrations increased with the dietary protein level up to CP45 diets. Muscle total EAA concentrations (%) of fish fed CP45 were significantly higher than those of fish fed CP30, CP35, CP50 and CP55, but there was no significantly different between those of fish fed CP40 and CP45. Muscle total NEAA concentration (%) of fish fed CP45 were significantly higher than those of fish fed CP30 and CP35 diets. Broken‐line analysis of WG suggested that the optimum dietary protein level could be 38.9% for maximum growth performance in juvenile beluga (1.3–77 g).